Evaluation of Urinary Tract Infection following Corticosteroid Therapy in Patients with Multiple Sclerosis Exacerbation. (1st February 2021) - Bazi, Aliyeh; Baghbanian, Seyed Mohammad; Ghazaeian, Monireh; Fallah, Sahar; Hendoiee, Narjes
Abstract : The first treatment for multiple sclerosis exacerbation is usually short-term intravenous methylprednisolone (IVMP), with or without a regimen of oral prednisone taper (OPT). This study aims to evaluate the effects of IVMP and OPT in comparison with IVMP alone in raising the risk of urinary tract infection (UTI) and posttreatment improvement of urinary tract symptoms in patients with relapsing-remitting multiple sclerosis. This double-blind randomized clinical trial was conducted on 56 people with multiple sclerosis relapse who had undergone methylprednisolone for 5 days. Patients were randomly split into two groups: oral prednisolone and placebo (tapering for 20 days). Demographic data, duration of multiple sclerosis, urinary tract symptoms, the Expanded Disability Status Scale (EDSS) score, and urine data were analyzed. The incidence of UTI in the intervention and control groups did not differ significantly (p = 560 ). However, the improvement of urinary tract symptoms in the intervention group was significantly more favorable than in the control group (p ≤ 0.001 ). Furthermore, administering OPT after IVMP did not increase the risk of UTI occurrence in patients with multiple sclerosis exacerbation. The urine analysis results did not show any differences at baseline and after the corticosteroid tapering regimen. Due to the risk of infection by corticosteroids, it is no longer necessary to do further urinary screening in this group of patients.